Nasab Anak Hasil dari Perkawinan Wanita Hamil Pandangan Majelis Ulama Indonesia (MUI) Kabupaten Langkat - M. Arif Maulana Karim; Syahrul Affan; Kamaliah R (Journal Smart Law, 2024)
This research discusses the opinion of the Indonesian Ulema Council (MUI) of Langkat Regency regarding the marriage of pregnant women, the birth status of children from marriages of pregnant women and the protection of these children. The research method used in this research is a descriptive qualitative research method with an empirical approach. The informants in this research were the Indonesian Ulema Council (MUI) Langkat Regency. Data collection uses observation, interviews and documentation. Data analysis by means of data reduction, triangulation and drawing conclusions. The results of the research explain that according to the view of the Indonesian Ulema Council (MUI) of Langkat Regency regarding the marriage of a pregnant woman is permissible, both with the man who impregnated her and with the man who did not impregnate her and the marriage is legal, adultery does not cause mushaharah to be prohibited. The view of the Indonesian Ulema Council (MUI) of Langkat Regency regarding the fate of children resulting from the marriage of pregnant women is that they state that the child is a child resulting from adultery and the treatment of them includes, among other things, children resulting from adultery who do not have a relationship between the child, marriage guardian, inheritance and support with the man who caused it. Apart from that, the birth of a child resulting from adultery only has a relationship of lineage, inheritance and support with the mother and her mother's family. Children resulting from adultery do not bear the sin of adultery committed by the person who gave birth to them. children from such marriages must receive the same treatment as other legitimate children, children of adultery have the right to live, have the right to education, have the right to be cared for by their parents, have the right to receive support from their biological father through a compulsory will and receive inheritance through their mother, by receiving treatment and (non-discrimination).